PENERAPAN HIDROTERAPI KAKI DENGAN REBUSAN JAHE MERAH UNTUK MENURUNKAN TEKANAN DARAH PADA PASIEN HIPERTENSI - Afifah Tria Ananda; Lucia Firsty Puspita Krisna (AKPER Pasar Rebo, 2025)
Abstract Background: Type 2 diabetes mellitus is a chronic disease characterized by increased blood sugar levels ranging from 90 to 95 percent, which occurs primarily in adults. Hydrotherapy, also known as water therapy, is one of the nonpharmacological interventions that aims to improve insulin sensitivity. This therapy has no side effects and can be performed independently at home. Objective: To determine the effect of hydrotherapy on reducing blood sugar levels in elderly people with type 2 diabetes. Methods: This study employed a literature review of five journals obtained through Google Scholar and ResearchGate, applying specific inclusion and exclusion criteria. Results: All five journals indicate that water hydrotherapy reduces blood sugar levels in elderly individuals with type 2 diabetes mellitus. Conclusion: Water hydrotherapy reduces blood sugar levels in elderly individuals with type 2 diabetes mellitus.. Keywords: Type 2 diabetes mellitus, water hydrotherapy, elderly